Rancang bagun aplikasi sewa ruang kantor - Indah Lestari; Sharyanto Sharyanto; Dwi Lestari (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
PT Wanamitra Permai is a company in the service sector, namely renting office buildings, palm towers which have 30 floors to be rented out to other companies. To ensure the Company's position as a leading mixed-used commercial property developer, the Company has operated 3 other buildings including hotels in Bali, created and focused on developing 2 new office buildings including 3 apartments. The Company's commitment and dedication to being the forefront and best in developing offices that are located in the middle of the city, comfortable, safe, classy and innovative without losing aesthetics and integrity guidelines according to the Company's principles are always a real contribution to responsible and environmentally friendly management.